Influence of cation substitution on ionic and electronic conductivity of (Cu1−𝑥Ag𝑥)7GeS5I mixed crystals - Pogodin Artem; Погодін Артем; Studenyak Viktor; Студеняк Віктор; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; Кохан Олександр; Yaroslav Studenyak; Студеняк Ярослав; Peter Kúš; et al. (My University, 2021)
Abstract. Impedance measurements of (Cu1−𝑥Ag𝑥)7GeS5I mixed crystals are carried out in the frequencyrange from 10 Hz to 300 kHz and in the temperature interval 292–383 K. The temperature andfrequency dependences of the electrical conductivity for (Cu1−𝑥Ag𝑥)7GeS5I mixed crystals arestudied. Based on the analysis of Nyquist plots and using the electrode equivalent circuits, thevalues of ionic and electronic components of the electrical conductivity are determined. Thecompositional behavior of the ionic and electronic conductivities, as well as the compositionalbehavior of their activation energies, are discussed. The ratio of ionic and electronic compo-nents of the conductivity for (Cu1−𝑥Ag𝑥)7GeS5I mixed crystals was analyzed.

Резюме. На монокристалiчних зразках твердих розчинiв(Cu1−𝑥Ag𝑥)7GeS5I були проведенi iмпеданснi вимiрюванняу дiапазонi частот вiд 10 Гц до 300 кГц та в iнтервалiтемператур 292–383 K. Вивчено температурну i часто-тну залежностi електропровiдностi твердих розчинiв(Cu1−𝑥Ag𝑥)7GeS5I. На основi аналiзу дiаграм Найквiстата з використанням електродних еквiвалентних схем буливстановленi значення iонної та електронної компонентелектропровiдностi. Дослiджено концентрацiйну поведiнкуiонної та електронної провiдностi, а також концентрацiй-ну поведiнку вiдповiдних енергiй активацiй. Проана-лiзовано спiввiдношення iонної та електронної компо-нент електропровiдностi для твердих розчинiв складу(Cu1−𝑥Ag𝑥)7GeS5I.
Вплив катiонного замiщення на iонну i електронну провiднiсть твердих розчинiв (Cu1−𝑥Ag𝑥)7GeS5I
Contents: https://ujp.bitp.kiev.ua/index.php/ujp/issue/view/106 Editorial Team: https://ujp.bitp.kiev.ua/index.php/ujp/about/editorialTeam
Keywords: mixed crystals; electrical conductivity; Nyquist plot; activation energy; compositional dependence